The Relationship of Student’s Readiness in Learning With Student’s Learning Achievement in History Class XI SMA Negeri Tegineneng - Ahmad Rudianto (PESAGI (Jurnal Pendidikan dan Penelitian Sejarah), 2020)
ABSTRACT          One of these factors is learning readiness. Based on the results of data analysis of research results and quantitative data analysis with correlation test and significance test, it was concluded that: "There is a positive and significant relationship between study readiness and learning achievement in history subjects for Class XI students at SMA Negeri 1 Tegineneng in the 2017/2018 academic year" . The formulation of the problem in this study is, Is there a positive and significant relationship between learning readiness and student achievement in history subjects in class XI at SMA Negeri 1 Tegineneng for the 2017/2018 academic year? The research objective was to determine whether there was a positive and significant relationship between learning readiness and student achievement in history subjects in class XI SMA Negeri 1 Tegineneng for the 2017/2018 academic year. The method used is a survey method. The research sample was taken using random sampling technique. Student learning readiness data were obtained from the results of questionnaires and learning achievement data were obtained from the results of the end of even semester 2017/2018. The correlation coefficient value was 0.77 which was greater than the value of the r-table value, which was 0.230 which indicated that there was a positive relationship between readiness. learning with learning achievement and significance test results. Keywords: Learning readiness, learning achievement, History Doi: http://dx.doi.org/10.23960/pesagi.v8.i2.2020.05